Optimalisasi Bimbingan Self Confidence sebagai Upaya Meningkatkan Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Moh. Ismail; Anis Fitriani (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
Confidence greatly affects student achievement. For this reason, self-confidence guidance for students is important to implement. This study aims to analyze the implementation of self-confidence guidance in improving student achievement in Islamic religious education subjects at SMP Negeri 2 Pucanglaban Tulungagung. This type of research used descriptive qualitative research. The results of the study show that: First, the learning achievement of students at SMP Negeri 2 Pucanglaban Tulungagung is still relatively low. Second, there are 6 forms of PAI teacher strategies through self-confidence guidance to students in improving learning achievement, namely: through learning, madin, memorizing, presentations in front of the class, awards for outstanding student champions, exemplary student awards. Meanwhile, guiding students' self-confidence in improving learning achievement is carried out through 3 stages, namely: preparation, implementation, evaluation stage. Third, the implications of the PAI teacher's strategy through self-confidence guidance to solid students improve student achievement. This is indicated by students being more confident in carrying out the learning process, especially in religious lessons. In essence, their learning achievement increases.